Aluminium–phosphate interactions in the rhizosphere of two bean species: Phaseolus lunatus L. and Phaseolus vulgaris L. (16th October 2013) - Mimmo, Tanja; Ghizzi, Massimiliano; Cesco, Stefano; Tomasi, Nicola; Pinton, Roberto; Puschenreiter, Markus
Abstract: BACKGROUND: Plants differ in their response to high aluminium (Al) concentrations, which typically cause toxicity in plants grown on acidic soils. The response depends on plant species and environmental conditions such as substrate and cultivation system. The present study aimed to assess Al–phosphate (P) dynamics in the rhizosphere of two bean species, Phaseolus vulgaris L. var. Red Kidney and Phaseolus lunatus L., in rhizobox experiments . RESULTS: Root activity of the bean species induced up to a sevenfold increase in exchangeable Al and up to a 30‐fold decrease in extractable P. High soluble Al concentrations triggered the release of plant‐specific carboxylates, which differed between soil type and plant species. The results suggest that P. vulgaris L. mitigates Al stress by an internal defence mechanism and P. lunatus L. by an external one, both mechanisms involving organic acids . CONCLUSION: Rhizosphere mechanisms involved in Al detoxification were found to be different for P. vulgaris L. and P. lunatus L., suggesting that these processes are plant species‐specific. Phaseolus vulgaris L. accumulates Al in the shoots (internal tolerance mechanism), while P. lunatus L. prevents Al uptake by releasing organic acids (exclusion mechanism) into the growth media. © 2013 Society of Chemical Industry